A Local Wisdom-Based Dance Learning Model for the Gross Motor Skills of 5- to 6-Year-Old Children in Preschool - Oky Fitriasari; Ratnasari Dwi Ade Chandra; Ahmad Afandi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
The suboptimal gross motor skills of children aged 5 to 6 years, as well as the limited utilization of learning based on local wisdom in the preschool setting, form the background of this study. This study aims to further examine a dance-based learning model rooted in local wisdom to improve the gross motor skills of children aged 5 to 6 years at the Al-Quran Asshiddiq Kindergarten. This study employed the Research and Development method using the ADDIE model. A total of 16 children aged 5–6 years were selected as research subjects. Data were collected through observation and documentation, which were subsequently analyzed by comparing pre-test and post-test results. The model’s feasibility, confirmed through prior expert verification, established its acceptability—specifically, the Gejik Dele dance learning model. The results of the study indicate that the Gejik Dele dance learning model was found to be effective in accelerating the improvement of motor skills in children aged 5–6 years, particularly in the domains of locomotor, non-locomotor, and manipulative movements. The implications of this study suggest that the integration of dance based on local wisdom can increase children’s engagement and provide a contextual learning experience. This study is limited by its small sample size and its focus on a single institution. The novelty of this study lies in the development of a Gejik Dele dance-based gross motor skills learning model—structured using the ADDIE approach—and the integration of local traditional values into the educational process for early childhood students.